If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(x + 1) = 10 Reorder the terms: 9x(1 + x) = 10 (1 * 9x + x * 9x) = 10 (9x + 9x2) = 10 Solving 9x + 9x2 = 10 Solving for variable 'x'. Reorder the terms: -10 + 9x + 9x2 = 10 + -10 Combine like terms: 10 + -10 = 0 -10 + 9x + 9x2 = 0 Factor a trinomial. (-5 + -3x)(2 + -3x) = 0Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-1.666666667, 0.6666666667}
| 12/1/3=36/y | | 3l+2w=800 | | 5t-7=54t | | 3(80-8x)=x-96 | | 2/3+5/15 | | 0=-5/4(y-6/5) | | 16/24=x/12 | | 3x-7/6=4x-7/6 | | -9(x+p)=x | | -13=17+x | | 3x-4=5(x+2) | | 4/5=n/20 | | (x+1)(x+3)=2(x+3) | | 2x+2/x-5=6 | | 5+(x-2/3)=(x+3/8) | | x2+2/x-5 | | 4x+9x=-39 | | b=7/4(j-49) | | 4x+2/2=17 | | 6x-2/5=8 | | 392+2x^2=1168 | | 3d=4(x-2) | | 18y+55x=2791 | | 1/55x+1/66x=1 | | -16-(-21)=x/6 | | 8x+20=3x+100 | | 1/2(4x+6)=1/3(9x-24) | | (5-y)-(6-y)=0 | | 9x-9/3=21 | | y=0.3x^2-4x+0.5 | | -5-2=13 | | 20x-10=14x+12 |